Risk taking : a guide to decision makers - Kindler, Herbert S. (Crisp Pub. Menlo ParkUS, 1999)
Provides guiding principles for taking risks; and presents a 3-phase process for making decisions that involve risk viz., (i) exploration; (ii) planning and preparation; and (iii) implementation, follow-up, and learning. Aims to enable decision makers to choose their risks. Advises on choosing change strategies and decision-making strategies in risky situations; and on how to recognize and overcome risk-taking barriers.